2021
DOI: 10.1186/s12888-021-03487-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian version of the Positive Mental Health Scale

Abstract: Background Positive mental health (PMH) is a factor of far-reaching salutogenetic importance. The present study aimed at validating the Persian version of the Positive Mental Health Scale (PMH-Scale). Methods Reliability and validity of the Persian version of the PMH-Scale were established in an Iranian student sample (N = 573). Internal consistency, convergent and discriminant validity were investigated, and exploratory factor analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In general, the PMH-Scale showed good psychometric properties. The results found in this study are similar to those of the original German version (Lukat et al, 2016) and very similar to the subsequent adaptations in other countries and cultures (Brailovskaia & Margraf, 2020; Çeçen & Vatandaşlar, 2021; Naghavi et al, 2021). In fact, a unidimensional structure of the scale was found with excellent model fit indices and high reliability, as well as convergent validity with optimism and resilience to suicide attempts and reattempts, and high negative convergent validity with anxiety.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In general, the PMH-Scale showed good psychometric properties. The results found in this study are similar to those of the original German version (Lukat et al, 2016) and very similar to the subsequent adaptations in other countries and cultures (Brailovskaia & Margraf, 2020; Çeçen & Vatandaşlar, 2021; Naghavi et al, 2021). In fact, a unidimensional structure of the scale was found with excellent model fit indices and high reliability, as well as convergent validity with optimism and resilience to suicide attempts and reattempts, and high negative convergent validity with anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…It was adapted during the COVID-19 pandemic for Iranian university students and showed excellent convergent validity with post-traumatic growth and social support and divergent validity with depression and post-traumatic stress disorder. It was able to discriminate between students at higher and lower risk of suicide (Naghavi et al, 2021). However, no studies have been found that have adapted this scale to the Spanish context (general population).…”
mentioning
confidence: 99%
“…However, considering the factor loading of item 46 is greater than 0.4 and the absolute fitting index was selected for the item to do confirmatory factor analysis, the fitting of the model is acceptable (Table 6 ), and the structure is ideal. The average variance extracted (AVE) of the combined reliability is preferably greater than 0.5, but if the residual variances (CR) of each dimension is greater than 0.6, an AVE greater than 0.4 is acceptable [ 27 ]. The CR values in this study are all greater than 0.6 and the AVE is greater than 0.4.…”
Section: Discussionmentioning
confidence: 99%
“…Positive Mental Health Scale [PMH-Scale; ( 25 ); Farsi version: ( 26 )]: The PMH-Scale assesses subjective and psychological aspects of well-being across nine items (e.g., “I manage well to fulfill my needs”; “I feel that I am actually well equipped to deal with life and its difficulties”) that are rated on a 4-point Likert-scale (0 = do not agree , 3 = agree ). Higher scores indicate higher levels of PMH.…”
Section: Methodsmentioning
confidence: 99%